microStretching® - A practical approach for recovery and regeneration - Apostolopoulos, N. (New Studies in Athletics, 2010)
Intense training and competition regularly expose the athlete`s body to stresses and strains exceeding the normal capacity to recover. Making sure that recovery and subsequent regeneration take place effectively is an integral part of maximising an athlete`s ability to perform to the best of his/her potential and should be the basis for planning the training programme.